(untitled) (Research, Society and Development, 2022)
This study aimed to report the case of a 26-year-old woman, brown, single, homeless and drug user, with a gestational age of 35 weeks, who did not undergo prenatal care or obtained any medical assistance during pregnancy, attended in the emergency department of a maternal and child reference institution in Belém in labor, where she was treated and underwent surgical delivery, giving birth to fraternal twins. Due to the clinical profile of those born, an investigation for Congenital Toxoplasmosis was carried out while still in the hospital. In both cases, seropositivity of anti-Toxoplasma gondii (T. gondii) IgM and IgG antibodies was detected in the first days of life. After diagnosis, specific therapy was instituted and both were referred to the referral center for infection in Belém, where they began follow-up at 2 months of age. The twins followed a routine investigation for the disease, which included fundoscopy, performed in the first months, computed tomography of the skull at 7 months and electroencephalogram at 1 year of life. This report shows a rare situation of Congenital Toxoplasmosis affecting two dizygotic twins. Factors such as maternal condition, virulence of the strain involved and/or the parasitic inoculum may have contributed to the systemic involvement of both to different degrees. Prevention measures at all levels are of paramount importance to reduce the risk of cases like this, as well as adequate support after birth, to minimize the sequelae of infection.